Enhanced conductivity of bacterial cellulose films reinforced with NH4I-doped graphene oxide - Torres, FG (2019)
This work was supported by the Vice-Rectorate for Research of the Pontificia Universidad Catolica del Peru and the National Council of Science, Technology and Technological Innovation of Peru (CONCYTEC/FONDECYT). The authors thank the staff at CAM-PUCP for help with the SEM images.